“eyes wide open”: E. W. Backus and The Pitfalls of Investing in Ontario’s Pulp and Paper Industry, 1902-1932 - Kuhlberg, Mark (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2005)
AbstractIt has long been argued that pulp and paper industrialists – especially Americans – could count on the cooperation of the provincial state as they established and expanded their enterprises in Canada in the first half of the twentieth century. The case of Edward Wellington Backus, an American industrialist, demonstrates that this paradigm does not explain the birth and dynamic growth of the newsprint industry in Ontario during this period. Backus rarely received the provincial government’s cooperation as he built paper plants in Fort Frances and Kenora. On the rare occasions when the politicians assisted him, they only did so within carefully prescribed limits. Backus’s story is significant because it indicates that it is time to reconsider the history of the political economy of Canada’s resource industries, at least as far as turning trees into paper is concerned.